1998
DOI: 10.1007/s002210050592
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological localization of brain regions involved in perceptual memory

Abstract: Event-related potentials (ERP) were recorded during perceptual discrimination and short-term memory, varying the interstimulus interval (1-10 s) in delayed spatial frequency discrimination. Accuracy of discrimination remained unimpaired across this time interval, but choice reaction times increased. A brain source localization (BESA) model showed that the activity of the parietal and right temporal sources increased with long retention intervals in a sequential activation pattern where a long-latency component… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…The general result of this research has been that the amount of time separating these two stimuli has little or no effect on the discrimination threshold (Bennett & Cortese, 1996;Blake, Cepeda, & Hiris, 1997;Greenlee, Rischewski, Mergner, & Seeger, 1993;Lee & Harris, 1996;Magnussen & Dyrnes, 1994;Magnussen & Greenlee, 1992;Magnussen, Greenlee, Asplund, & Dyrnes, 1990, 1991Magnussen, Greenlee, & Thomas, 1996;Magnussen, Idås, & Myhre, 1998;Magnussen, Landrø, & Johnsen, 1985;Nilson & Nelson, 1981;Regan, 1985;Vogels & Orban, 1986). These findings have been taken as evidence for very good or even "perfect" memory (Magnussen, 2000;Magnussen & Greenlee, 1999;Reinvang, Magnussen, Greenlee, & Larsson, 1998). This interpretation carries with it two assumptions: (1) that memory has a limiting influence on discrimination performance and (2) that the memory happens to be so accurate that it does not degrade the performance.…”
mentioning
confidence: 81%
“…The general result of this research has been that the amount of time separating these two stimuli has little or no effect on the discrimination threshold (Bennett & Cortese, 1996;Blake, Cepeda, & Hiris, 1997;Greenlee, Rischewski, Mergner, & Seeger, 1993;Lee & Harris, 1996;Magnussen & Dyrnes, 1994;Magnussen & Greenlee, 1992;Magnussen, Greenlee, Asplund, & Dyrnes, 1990, 1991Magnussen, Greenlee, & Thomas, 1996;Magnussen, Idås, & Myhre, 1998;Magnussen, Landrø, & Johnsen, 1985;Nilson & Nelson, 1981;Regan, 1985;Vogels & Orban, 1986). These findings have been taken as evidence for very good or even "perfect" memory (Magnussen, 2000;Magnussen & Greenlee, 1999;Reinvang, Magnussen, Greenlee, & Larsson, 1998). This interpretation carries with it two assumptions: (1) that memory has a limiting influence on discrimination performance and (2) that the memory happens to be so accurate that it does not degrade the performance.…”
mentioning
confidence: 81%
“…Figure 1b illustrates the results obtained in this type of experiment, plotting choice reaction times (RT) for delayed spatial frequency discrimination as a function of the ISI. No change in RT is observed during the ®rst three seconds, but for longer retention intervals, RTs increase, and at 10 s ISI, RTs are prolonged by 120± 400 ms, depending on the experimental conditions Reinvang, Magnussen, Greenlee, & Larsson, 1998). Control experiments con®rmed that the increase is associated with the delayed discrimination task .…”
Section: Dissociation Of Perception and Memorymentioning
confidence: 94%
“…The ERP analysis thus identi®es a parietal source which may be directly related to the retrieval of spatial frequency information in perceptual shortterm memory. Reinvang et al (1998) further found that adding a frontal source to the analysis did not improve the solution in the memory condition. This is consistent with the results of PET studies of memory which indicate that the frontal lobes are involved in the retrieval of visual information in episodic memory tests and tests that may rely on episodic memory such as match-to-sample, but not in priming (Cabeza & Nyberg, 1997), and provides further evidence that perceptual memory is part of the non-conscious PRS.…”
Section: Brain Mechanisms Of Perceptual Memorymentioning
confidence: 94%
See 1 more Smart Citation
“…At least seven 5-HT receptor families (5-HT 1-7 ) have been identified (Hoyer et al, 1994). Among the 5-HT receptor families, the 5-HT 6 receptor is localized primarily in the central nervous system and in regions such as the cerebral cortex, nucleus accumbens, caudate-putamen, striatum, and hippocampus (Roberts et al, 2002;Hirst et al, 2003;Marazziti et al, 2012) that are associated with cognition and memory (Nyberg et al, 1996;Reinvang et al, 1998;Burgess et al, 2001). In experimental models, 5-HT 6 antagonists have demonstrated the ability to increase brain levels of acetylcholine and glutamate (Dawson et al, 2000;Riemer et al, 2003;Marcos et al, 2006) and to improve cognitive functions in animal models (Lindner et al, 2003;Foley et al, 2004;Lieben et al, 2005;Arnt et al, 2010;Mohler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%